Biochemical changes in some trace elements, antioxidant vitamins and their therapeutic importance in prostate cancer patients - Onyema-iloh, Bridget Obiageli; Meludu, Samuel C; Iloh, Emmanuel; Nnodim, Johnkennedy; Onyegbule, Onyema; Mykembata, Blessing (Asian Journal of Medical Sciences, 2014)
Aim: This study was conducted to evaluate the serum levels of some trace-elements (zinc, copper and selenium) and antioxidant vitamins (vitamin A, C and E) in prostate cancer patients. Method: A total of 50 prostate cancer patients aged 50-70 years with PSA > 4.0 ng/dl were recruited for the study while 50 apparently healthy individual were used as control subjects. Zinc, copper and selenium were determined using atomic absorption spectrophotometer while vitamin A, C and E were determined using high performance liquid chromatography. Result: The result showed that the mean levels of Se (0.77±0.26), Zn(147.75±42.05) were significantly lower (p <0.05) when compared with the control (1.47±0.13) and (168.78±59.80) respectively. The serum copper level (187. 76±66.05) was significantly higher (p<0.05) when compared with control (126.40±31.24).The antioxidant vitamin A (0.42±0.19), vitamin C (3.62±1.81) and vitamin E (0.39±0.13) were Significantly lower p(<0.05) when compared with the control (0.68±0.32)(12.16±4.07) and (1.40±0.16) respectively. Concusion: The decreased trace elements and antioxidant vitamins may be associated with high free radicals generated due to oxidative stress in prostate cancer patient. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10799 Asian Journal of Medical Sciences Vol.6(1) 2015 95-97